PERANAN ANGGARAN BIAYA OPERASIONAL DALAM MENINGKATKAN EFISIENSI PADA PT. SOP SUMSUM LANGSA - Baene, Rosmawati; Nasution, Ilham Ramadhan; Atika, Diyah (Worksheet : Jurnal Akuntansi, 2023)
Company management, one of the most important issues is the role of the operational costbudget in a company. Measurement of a company's financial performance will showwhether or not a company is healthy in carrying out its operational activities during a certainperiod. This study aims to determine the role of the operational cost budget in increasing theefficiency of PT. Sop Sumsum Langsa has been implemented as in increasing the efficiencyof the company. This research method using descriptive study. The type of data used isprimary and secondary data. Data collection techniques were carried out by interviews anddocumentation. The results showed that the realization of the operational cost budget thathad been set at PT. Sop Sumsum Langsa was good (95.29%) where each section carried outoperational activities based on the budget that had been set by the company. The operationalcost budget has a role as a means of controlling operational costs and avoiding excessive useof costs, as well as controlling an activity so that it does not deviate from the budget that hasbeen made as minimum as possible.